Interplay between caspase, Yes-associated protein, and mechanics: A possible switch between life and death?. (December 2020) - Kabigting, Jessica Evangeline Tan; Toyama, Yusuke
Abstract: Organism development requires fine-tuning of the cell number by apoptosis and cell division, as well as proper cell fate specification. These processes are achieved through the integration of intracellular signals and intercellular interactions with neighboring cells as well as the extracellular environment. Apoptosis, a form of cell death typically associated with development and homeostasis, is mainly regulated by the caspase family of proteases. Although caspases are known to initiate and execute apoptosis, it is also known that low caspase levels have a broad spectrum of nonapoptotic functions, including differentiation and organ growth. These different roles of caspases raise intriguing questions: how are caspase levels regulated and what defines the balance between life and death? In this review, we focus on some recent findings that highlight how nonlethal levels of caspase activity, transcriptional coregulator Yes-associated protein (YAP), and mechanical factors influence each other in determining cell fate. We further discuss a possibility that the mechanical signals encountered by cells could regulate the level of caspase activity by mechanics through YAP and, in turn, how this determines whether a cell is susceptible or resistant to undergoing apoptosis in response to cell death stimuli.